Carbon dots from roasted mackerel (scomberomorus niphonius) for free radical scavenging. (August 2019) - Li, Jiaqi; Cao, Lin; Li, Dongmei; Yu, Chenxu; Tan, Mingqian
Abstract: Foodborne nanoparticles produced from food components during thermal processing have received attention due to their particular properties. Herein, the presence of fluorescent carbon dots (CDs) was reported from mackerel flesh roasted at 230 °C in an electronic oven, and the CD capability for free radical scavenging was investigated. The average size of the CDs was about 2.2 nm with a size distribution in the range of 0.9–3.5 nm as characterized with transmission electron microscopy (TEM). X-ray photoelectron spectroscopy (XPS) showed that the mackerel CDs mainly contain C, N and O. Fourier transform infrared (FTIR) analysis showed the existence of hydroxyl, amino, and carboxyl groups on the mackerel CD surface. The fluorescence lifetime was about 9.1 ns. Two absorption peaks at 277 and 328 nm were observed in UV–vis spectra, which are assigned to the π-π* and n-π* charge-transfer, respectively. The mackerel CDs showed excellent photostability in various metal ion solutions and pH environment. In addition, these CDs exhibited strong dose-dependent scavenging capability for hydroxyl radicals (·OH) and methyl radicals (·CH3 ) produced from methylene blue (MB)/visible-light photosensitization system. The free radical scavenging properties make the mackerel CDs capable of protecting against oxidative stress after they are exposed to biosystem. Graphical abstract: Image 1 Highlights: Foodborne carbon dots (CDs) were first found from roasted mackerel. The CDs with an average size of 2.2 nm can emit tunable fluorescence. The mackerel CDs mainly contain C, N, O and H. The CDs exhibited strong scavenging capability for free radicals.